2017
DOI: 10.1055/s-0043-122223
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Significance of MMPs in Synovial Fluid, Serum and PBMC Culture Supernatant Stimulated by LPS in Osteoarthritis Patients With or Without Diabetes

Abstract: High levels of MMP-1, -7, -8, -9, -10, and -12 in the synovial fluid might be one of important reasons that diabetes patients are more frequently suffered from OA. Inflammation-induced malfunction of mononuclear cells would stimulate MMP-8 and -9 secretion to various extents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…7,8 Some of these MMPs have been shown to be upregulated by inflammatory cytokines or mononuclear cells. 9,10 It has also been shown that synovitis upregulates MMP expression and therefore perpetuates the degradation characteristic of progressive OA. 11 Normally MMPs are regulated in tissues by tissue inhibitors of metalloproteinases (TIMPs).…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Some of these MMPs have been shown to be upregulated by inflammatory cytokines or mononuclear cells. 9,10 It has also been shown that synovitis upregulates MMP expression and therefore perpetuates the degradation characteristic of progressive OA. 11 Normally MMPs are regulated in tissues by tissue inhibitors of metalloproteinases (TIMPs).…”
Section: Introductionmentioning
confidence: 99%
“…High molecular weight HA also has anti-inflammatory properties [130]; its localisation at the cartilage surface contributes to joint lubrication. Lubricin in the surface regions of cartilage also binds to a number of cartilage proteins [131] contributing to joint lubrication, and the retention of lubricin at the cartilage surface [132] and may promote cartilage regeneration [133,134,135].…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In addition, our previous study demonstrated that expressions of matrix metalloproteinases (MMPs) were significantly elevated in type 2 DM than those in diabetes-free OA patients and healthy controls. 9 Also, the phenomenon that high concentration of Glc affects chondrocytes and cartilage metabolism has also been observed in experimental studies. One study found that 25 nM Glc attenuated proteoglycan synthesis induced by IGF-1 in rabbit chondrocytes.…”
Section: Introductionmentioning
confidence: 88%